2011
DOI: 10.1111/j.1600-0765.2011.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Statins regulate interleukin-1β-induced RANKL and osteoprotegerin production by human gingival fibroblasts

Abstract: IL-1β significantly increased OPG production by HGFs. The statins differed minimally in their effects on OPG and RANKL production by resting and IL-1β-activated HGFs. Both statins increased constitutive RANKL/OPG ratios, but generally not IL-1β-stimulated ratios. Thus, statins may influence the production of RANKL and OPG by HGFs to favor bone catabolism, under noninflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
9
0
1
Order By: Relevance
“…Experimental studies also found that its local application alone or in combination with bisphosphonates exerts positive effects on bone formation 34 . The direct relationship between statin consumption and OPG concentrations evidenced in the present study was also observed previously in vitro 35‐37 . The improved AL values in the S group in the present study may be explained by their increased OPG concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…Experimental studies also found that its local application alone or in combination with bisphosphonates exerts positive effects on bone formation 34 . The direct relationship between statin consumption and OPG concentrations evidenced in the present study was also observed previously in vitro 35‐37 . The improved AL values in the S group in the present study may be explained by their increased OPG concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…These beneficial effects, which are independent of their lipid-lowering effects, include anti-inflammatory,[22] immune-modulatory,[2324] antioxidant,[25262728] antithrombotic, and endothelium stabilization actions. [29] They also cause the inhibition of MHC-II expression, and inhibition of release of pro-inflammatory cytokines such as IFN-γ, TNF-α, IL-1 β, and IL-6 from various cell types, thereby, providing immunomodulatory effects as well. [23] Statins also cause inhibition of NADPH, a major source of oxidant production, thereby providing antioxidant effect,[25] as well as angiogenesis promotion and increase of osteoblastic differentiation, inducing bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may suggest the immunomodulatory effect of SMV as observed in various other studies also. [232429] In addition, it may be interpreted that the significant reduction in PPD is not only due to the shrinkage of the soft tissue but also in response to SMV. This was further substantiated by getting a significant correlation between reduction in PPD and gain in CAL signifying the gain in attachment was taking place along with shrinkage of soft tissue, side by side [Table 6].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs were tested because BPs have been shown to be potent inhibitors of osteoclast‐mediated bone resorption . Moreover, in addition to prevention of cardiovascular disease, statins have shown important pleiotropic effects, such as anti‐inflammatory and antiresorptive effects .…”
Section: Discussionmentioning
confidence: 99%